1928
DOI: 10.1037/h0076053
|View full text |Cite
|
Sign up to set email alerts
|

The effects of continuous work upon output and feelings.

Abstract: In the course of an investigation of the effects of continuous physical and mental work 1 a series of reports was obtained from the subjects doing mental work in regard to their feelings. The relation between changes m output of work and changes in the feehngs will be discussed in this paper.Four forms of mental work 2 were used, each continued for approximately five and one-half hours, or until the subject refused to work longer. They were:1. Continuous addition which consists in adding to a twoplace number f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

1956
1956
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…The first instrument for assessing tiredness was developed during the 1920s. [18] Now, there are numerous methods and instruments for assessing fatigue, such as Bristol Rheumatoid Arthritis Fatigue-Multidimensional Questionnaire, Chalder Fatigue Questionnaire, Checklist Individual Strength (CIS20R and CIS8R), Fatigue Severity Scale, Multidimensional Fatigue Inventory, and Multidimensional Assessment of Fatigue (MAF) scale. [19]…”
Section: Introductionmentioning
confidence: 99%
“…The first instrument for assessing tiredness was developed during the 1920s. [18] Now, there are numerous methods and instruments for assessing fatigue, such as Bristol Rheumatoid Arthritis Fatigue-Multidimensional Questionnaire, Chalder Fatigue Questionnaire, Checklist Individual Strength (CIS20R and CIS8R), Fatigue Severity Scale, Multidimensional Fatigue Inventory, and Multidimensional Assessment of Fatigue (MAF) scale. [19]…”
Section: Introductionmentioning
confidence: 99%
“…He found no performance difference between the groups. Poffenberger (1928) studied subjects (age unstated) who worked continuously for 5½ hours on one of four kinds of tasks (addition, sentence completion, intelligence test items, or judging compositions). Feelings consistently declined, but only arithmetic performance declined; performance increased over the time on the intelligence test tasks.…”
Section: Introductionmentioning
confidence: 99%
“…The possibility of establishing a subjective measure of fatigue has seemed unpromising because of the difficulty of treating affective responses in a simple, quantitative manner. Although several studies employing measures of subjective fatigue have been reported in the literature (8)(9)(10)(11)(12)(13)(14) it has only been within the last few years that any study has been designed primarily to develop a fatigue scale. Frazier (15) attempted to scale 70 items by Guttman's method (16) but was unsuccessful.…”
Section: Introductionmentioning
confidence: 99%